Ответ:
1) у = -7
2) у = 14
Объяснение:
1) у = (-14 : 2) / (2 : 2) = -7 / 1 = -7
2) у = -14 : (-1) = 14
[tex]y = - \frac{14}{x} \\ 1) \: x = 2 \\ y = - \frac{14}{2} = - 7 \\ 2) \: x = - 1 \\ y = - \frac{14}{ - 1} = - ( - 14) = 14[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
1) у = -7
2) у = 14
Объяснение:
1) у = (-14 : 2) / (2 : 2) = -7 / 1 = -7
2) у = -14 : (-1) = 14
[tex]y = - \frac{14}{x} \\ 1) \: x = 2 \\ y = - \frac{14}{2} = - 7 \\ 2) \: x = - 1 \\ y = - \frac{14}{ - 1} = - ( - 14) = 14[/tex]